Respuesta :
Answer:
Step-by-step explanation:
Simplifying
5n + 4 = 7(n + 1) + -2n
Reorder the terms:
4 + 5n = 7(n + 1) + -2n
Reorder the terms:
4 + 5n = 7(1 + n) + -2n
4 + 5n = (1 * 7 + n * 7) + -2n
4 + 5n = (7 + 7n) + -2n
Combine like terms: 7n + -2n = 5n
4 + 5n = 7 + 5n
Add '-5n' to each side of the equation.
4 + 5n + -5n = 7 + 5n + -5n
Combine like terms: 5n + -5n = 0
4 + 0 = 7 + 5n + -5n
4 = 7 + 5n + -5n
Combine like terms: 5n + -5n = 0
4 = 7 + 0
4 = 7
Solving
4 = 7
5n + 4= (n + 1) -2n
4=(n + 1) - 2n - 5n
4= n + 1 - 2n-5n
4-1=n-2n-5n
3=-6n
3\-6 =-6n/-6
-1/2=n
4=(n + 1) - 2n - 5n
4= n + 1 - 2n-5n
4-1=n-2n-5n
3=-6n
3\-6 =-6n/-6
-1/2=n